682 ENDOFLIP TAILORED PER-ORAL ENDOSCOPIC MYOTOMY (POEM): EXPERIENCE IN TWO UK CENTRES. (17th September 2021) - Knight, William; Kandiah, Kaveetha; Couch, Jennifer; Tewari, Nila; Ragunath, Krish; Catton, James; Botha, Abraham
Abstract: : Per-oral endoscopic myotomy (POEM) is an effective treatment for achalasia. Efficacy is equivalent to Laparoscopic Heller's myotomy with the advantage of minimal access and shorter length of stay. Post-operative reflux rates are higher in POEM. The Functional Luminal Imaging Probe (FLIP) allows the measurement of lower oesophageal distensibility during per-oral endoscopic myotomy. In theory, this enables the operator to tailor the myotomy to ensure adequate distensibility whilst minimising post-operative reflux risk. Methods: Two prospectively collected POEM databases were analysed from 2 UK tertiary upper GI centres. The operators in each centre used intraoperative FLIP measurements to ensure adequate myotomy. Outcome measures included Eckardt score (where ≤3 indicated clinical success) and proton pump inhibitor use (PPI), collected at the first post-operative appointment. Length of stay was recorded, as were complications. Results: 142 patients underwent POEM between 2015 and 2019 with 90% (128/142) clinical success. This improved to 93% (68/73) in the latter half of each series. 79% of the poor responders had previous interventions compared to 55% of responders (p = 0.09). Average post myotomy distensibility was 5.2 mm2/mmHg in responders and 3.11 in non-responders(p = 0.11). DI of >4.5 mm2/mmHg was associated with 100% clinical success. Myotomy length of <7 cm was associated with 93% clinical success and 40% post op PPI use compared to 60% with longer myotomies. There were 2 type IIIa, 2 type IIIb and one type IV Clavien-Dindo complications. Conclusion: This study represents one of the largest UK series of FLIP tailored per-oral endoscopic myotomy. FLIP allows intraoperative monitoring of oesophageal distensibility allowing tailoring of myotomies. Tailored myotomies ≤6 cm were effective and were associated with less PPI use post operatively. Early referral of patients to high volume centres, where myotomies can be tailored using FLIP may lead to improved outcomes. More collaborative data from high volume centres is needed to decipher optimal myotomy profiles.